2017
DOI: 10.1136/bmjopen-2017-018280
|View full text |Cite
|
Sign up to set email alerts
|

Evidence assessing the diagnostic performance of medical smartphone apps: a systematic review and exploratory meta-analysis

Abstract: ObjectiveThe number of mobile applications addressing health topics is increasing. Whether these apps underwent scientific evaluation is unclear. We comprehensively assessed papers investigating the diagnostic value of available diagnostic health applications using inbuilt smartphone sensors.MethodsSystematic Review—MEDLINE, Scopus, Web of Science inclusive Medical Informatics and Business Source Premier (by citation of reference) were searched from inception until 15 December 2016. Checking of reference lists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 42 publications
0
47
0
4
Order By: Relevance
“…There are over 165 000 healthcare mobile applications available on the market, some of which provide the probability or risk of photographed melanocytic skin conditions being benign or malignant . Buechi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are over 165 000 healthcare mobile applications available on the market, some of which provide the probability or risk of photographed melanocytic skin conditions being benign or malignant . Buechi et al .…”
Section: Discussionmentioning
confidence: 99%
“…There are over 165 000 healthcare mobile applications available on the market, some of which provide the probability or risk of photographed melanocytic skin conditions being benign or malignant . Buechi et al . conducted a meta‐analysis of smartphone applications and reported that the pooled sensitivity and specificity of studies assessing melanoma were 73% and 84%, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…[50] Some authors demonstrate that these applications have a sensitivity for melanoma of 73% and specificity of 83%, whereas dermatologists have sensitivity of 88% and specificity of 97%. [51] Other authors demonstrate that smartphone apps have scarce scientific evidence, studies are small and have low methodological quality and only one-third of the app has assessed diagnostic accuracy [52]. Thus, new apps may come to the market, which may significantly aid the diagnosis of early NM.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Research with diagnostic studies are missing since most apps target a diagnostic problem without the scienti c basis. 22 Our study is a good example of how a mHealth solution might be integrated into the occupational health programs (OHP) and prevention programs. The results showed signi cant changes in levels of stress hormones which could be due to increased level of physical activity and frequency of deep relaxation during a regular week for employees.…”
Section: Discussionmentioning
confidence: 99%